2010
DOI: 10.1016/j.bbabio.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid-triggered energy dissipation in phycobilisomes of Synechocystis sp. PCC 6803 diverts excitation away from reaction centers of both photosystems

Abstract: Cyanobacteria are capable of using dissipation of phycobilisome-absorbed energy into heat as part of their photoprotective strategy. Non-photochemical quenching in cyanobacteria cells is triggered by absorption of blue-green light by the carotenoid-binding protein, and involves quenching of phycobilisome fluorescence. In this study, we find direct evidence that the quenching is accompanied by a considerable reduction of energy flow to the photosystems. We present light saturation curves of photosystems' activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Our results clearly demonstrate that OCP protects the photosystems and cells via two different mechanisms: by quenching of excess excitation energy (Wilson et al, 2006;Rakhimberdieva et al, 2010;Tian et al, 2011), and thereby decreasing charge separations at the reaction centers, and by quenching 1 O 2 , which is formed during the light reactions that still occur in the reaction centers and in the antennae. These two protecting mechanisms complement each other.…”
Section: Ocpmentioning
confidence: 86%
“…Our results clearly demonstrate that OCP protects the photosystems and cells via two different mechanisms: by quenching of excess excitation energy (Wilson et al, 2006;Rakhimberdieva et al, 2010;Tian et al, 2011), and thereby decreasing charge separations at the reaction centers, and by quenching 1 O 2 , which is formed during the light reactions that still occur in the reaction centers and in the antennae. These two protecting mechanisms complement each other.…”
Section: Ocpmentioning
confidence: 86%
“…It has been recently shown that, in cyanobacteria, like in plants, there exists a photoprotective process that decreases the energy transfer between the antenna and the reaction centers by increasing thermal dissipation (8)(9)(10)(11)(12)(13). However, this mechanism is not triggered by a lowering of the luminal pH, as occurs in plants;…”
mentioning
confidence: 97%
“…It results in an increase of the thermal dissipation of the energy absorbed by the PBs (14). A concomitant decrease of the PB fluorescence emission and of the energy transfer from the PB to the reaction centers also occurs (9,14). In mutants in which the OCP was absent (12) or unable to form or stabilize the red OCP form (14,15), blue-green light did not induce fluorescence quenching or the photoprotective mechanism.…”
mentioning
confidence: 99%
“…The latter is the highest peak corresponding to PSI-associated Chl a and it is shifted by 2-3 nm to the blue region comparing with that of WT, most probably as a consequence of missing carotenoids. The peak at 650 nm is emitted by phycocyanin (MacColl and Guard-Friar 1987) and the peak at around 685 nm is emitted either by PSII-associated Chl a or by APC-B and APC-L CM (Rakhimberdieva et al 2010), terminal emitters of PBSs. These two increased fluorescence emission peaks suggested that the linear electron transfer between PBS and PSI could not function efficiently.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…The phenomenon is known as non-photochemical quenching (NPQ) in cyanobacteria (Rakhimberdieva et al 2010) 1.1.2 Major photosynthetic complexes in thylakoid membrane…”
Section: Light Harvesting Antenna Systemmentioning
confidence: 99%